Label-Free Determination of PSA and Free PSA Using MA-SERS - Chaloupková, Zuzana; Medříková, Zdenka; Král, Milan; Šedajová, Veronika; Ranc, Václav (Frontiers in Analytical Science, 2022)
Prostate cancer is one of the compelling types of cancer diagnosed in men. Development of screening analytical methods which provide fast and reliable results is thus demanding. Currently applied methods are usually based on the determination of serum prostate specific antigen (PSA), where several limitations were identified. However, scientific reports have shown a direct correlation between the percentage of freePSA and prostate volume, and indirect correlation between the unfavourable course of the disease of prostate cancer and the percentage of free PSA in men with elevated PSA levels. Parallel analysis of PSA and freePSA presents an interesting alternative. Here, we present a new analytical method for a parallel analysis of PSA and freePSA in a whole human blood based on MA-SERS. The method is based on magnetic Fe3O4@Ag nanocomposite functionalized using anti-PSA. The method can distinguish between levels of PSA and freePSA within a single analytical run with limits of detection 0.62 ng/mL for PSA and 0.49 ng/mL for freePSA, respectively.